What is the Global View of Women's Leadership? Sentiment Analysis based on Meta-Analysis - Laela, Ela; Taufiq, Adhitya Rahmat; Mandasari, Andina Eka (Jurnal Manajemen Indonesia, 2024)
This research aims to analyze literature about leadership women and integrate diverse perspectives with meta-analysis and sentiment analysis. This research uses a design study combined qualitative with analysis statistics descriptive for meta-analysis and analysis sentiment. The search sample uses a purposive sampling technique. This study analyzes articles on Dimension.ai metadata about women's leadership from 2015 to 2022. Keywords used for data collection, namely "Women Leadership". The results of the meta-analysis show the development of women's leadership research that contributes to the limitations of knowledge. Analysis results in sentiment show that expert opinion about women's leadership varies, with positive sentiment by 30%, negative sentiment by 30%, and neutral sentiment by 40%. This research is the first to discuss the view of a global evolution in women's leadership research and produces consequences that contribute to achieving the SDGs.